PERANCANGAN ANIMASI 3D JALAN BYPASS SEDAU KE SEI RASAU MENGGUNAKAN METODE MDLC (MULTIMEDIA DEVELOPMENT LIFE CYCLE) - Agus Tulus; Noferianto Sitompul; U Heri Mulyanto; Vanie Wijaya; Naufal Aulia Fiermeiza; Lang Jagat; Sri Wahyuni; Erifa Syahnaz (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The construction of the Singkawang Sedau to Sei Rasau Bypass Road is an important infrastructure project to reduce congestion and facilitate transportation flow. However, the delivery of information on this project is still limited to technical documents and two-dimensional images that are less capable of des the real conditions, making it difficult for the general public to understand. To answer this problem, a 3D animation design was carried out using the MDLC (Multimedia Development Life Cycle) method, which consists of six stages: concept, design, material collection, creation, testing, and distribution. This study aims to design a 3D animation of the Singkawang bypass road (Sedau - Sei Rasau) using the MDLC method. It is expected to contribute to infrastructure development in the Singkawang area, as well as provide a positive impact on the community and regional development. The final result of this design is a 5:20-minute 3D animation of the Singkawang Bypass Road, which shows the condition of the road construction plan from Sedau to Sei Rasau and is considered effective in conveying information and facilitating public understanding of the development project. Questionnaire measured using a Likert scale by two subject matter experts and two media experts, yielded scores of 88% and 96%, respectively. A questionnaire was also administered to 30 members of the public, resulting in a score of 86%. The test results showed that all respondents gave it a very good rating, and this 3D animation is worthy of publication and presentation as an information and reference medium that can be used by the Singkawang Public Works and Public Housing Agency to continue the construction of the bypass road.